Economic and Social Resilience of Muslim Families during a Pandemic and Its Implications for Family Counseling - Desri Jumiarti; Rahmatul Hayati; Emeliya Hardi; Eko Sujadi; Zahara Febrianti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Abstract: The purpose of this study was to provide resilience to the economic and social resilience of Muslim families during the pandemic and their interactions with family counseling in Pantai Cermin District, Solok Regency. This study uses a quantitative descriptive approach. The population of the study was the entire community of Pantai Cermin sub-district, Solok Regency. Sampling is by using a cluster random sampling system, by categorizing jorong which is rarely populated with densely populated areas. Some samples are chosen randomly or randomly from some of these clusters. Respondents were given a family resilience questionnaire to fill out in order to collect data for this study. Validating Instruments with an expert judgment system. The results showed that 46.1% of families had low economic resilience and 19.4% of families had low social security. This shows that there are still many families who have low economic resilience and there are still families who have low social resilience. As a result, it can be said that it is very necessary for the family to have economic and social resilience in facing various problems and under any conditions. In this case, it has very implications for family counseling, because through family counseling, assistance can help in solving it. Through family counseling, families are able to overcome their problems and are expected to create family resilience.